Correlation between the Pre-Analytical Stage and Quality of Breast Histopathology Specimen - Kurniawaty, Nyiayu Fauziah; Krisna Murti; Nora Ramkita; Sandria (Jurnal RSMH Palembang, 2024)
The histopathology preparations procedure in the Anatomic Pathology Laboratory consists of three stages: pre-analytic, analytical and post-analytic. Errors in the pre-analytic process can affect the quality of histopathology preparations, thereby affecting diagnosis and patient management. The length of fixation and the large size of tissue lamellae are variables in the pre-analytic process that influence the quality of histopathological preparations. The aim of this study is to determine the relationship between the length of fixation and the size of large tissue lamellae on the quality of histopathological preparation. A cross-sectional study was conducted on medical record data of histopathological examination of breast tissue examined at the Barokah Palembang Anatomical Pathology Laboratory between January - December 2022. There were 37 cases of histopathological specimens that met the inclusion criteria, of which 3 cases were underfixed, 13 cases were overfixed and the rest were normal. One case from the underfixation, 20 cases from the normal fixation and 3 from the overfixation group were included in the good specimen quality category. The Spearman test showed that there was a significant relationship between normal fixation and good specimen quality (p=0.00217). Of the 37 research subjects, there were 18 subjects who were categorized as good lamellation. When related to specimen quality, good lamellation is associated with good specimen quality (p=0.02161). The correct fixation and lamellation during the pre-analytic phase are associated with good specimen quality.